Noise as Dysappearance: Attuning to a Life with Type 1 Diabetes. (December 2019) - Kingod, Natasja; Cleal, Bryan
In this article, we use noise as a metaphor for the overload of information – embodied, technological and online social – that characterizes life with type 1 diabetes. Noise illustrates embodied sensations of fluctuating blood glucose, measurement problems and alarms from digital self-care devices and irrelevant or emotionally disturbing posts on Facebook. Attunement is crucial to the quality of self-care achieved by individuals and comprises: (1) developing skills to receive clear signals from the body, (2) adjusting and individualizing self-care technologies to bodies and daily lives and (3) discerning appropriate distracting and unhelpful self-care information. Ideally, life with type 1 diabetes is harmonious, with clear messages from bodies, technologies and Facebook that enable better self-care.